The Concizumab Pen-Injector is Easy to Use and Preferred by Hemophilia Patients and Caregivers: A Usability Study Assessing Pen-Injector Handling and Preference [Corrigendum] - Kahr Rasmussen N; Berg B; Christiansen ASL; Neergaard JS; Ter-Borch G; Hildebrand EA; Gonczi M; Sparre T (Patient Preference and Adherence)
Kahr Rasmussen N, Berg B, Christiansen ASL, et al. Patient Prefer Adherence. 2024;18:1713—1727. Page 1719, Table 4, Range column, Total row under the Time to prepare and inject section, the text “0 min 29s–4 min 7s” should read “0 min 29s–4 min 3s”. The correct table is as follows.